2020
DOI: 10.5505/anatoljfm.2020.22932
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxoplasma gondii, Rubella virus and Cytomegalovirus Infections in Pregnant Women

Abstract: Primary infection agents occurring during pregnancy and causing congenital anomalies are Toxoplasma gondii (T.gondii), rubella virus and cytomegalovirus (CMV). It was revealed that these agents infected the fetus by crossing the placenta and increased the rate of fetal morbidity and mortality. This study aimed to investigate the relationship between seroprevalences of T. gondii, rubella virus and CMV antibodies. Methods:The results were retrospectively evaluated. Pregnant women's serum samples sent to the Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…Although there are differences between regions in studies conducted in Turkey, generally CMV IgG positivity is over 90%. [11] In our study,CMV IgG positivity was found to be 98.7%.CMV infection is usually asymptomatic and transmissible to the fetus, some suggest that all women of childbearing age should know their CMV serostatus. [21][22][23][24] But on the other hand, American College of Obstetricians and Gynecologists [25] and Society for Maternal-Fetal Medicine, [26] recommend against routine serologic screening for CMV since there is no vaccine is available to prevent infection in seronegative women and in seropositive pregnant women, it is difficult to distinguish between primary infection, reinfection or reactivation and it is also diffucult to determine the time of the infection.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…Although there are differences between regions in studies conducted in Turkey, generally CMV IgG positivity is over 90%. [11] In our study,CMV IgG positivity was found to be 98.7%.CMV infection is usually asymptomatic and transmissible to the fetus, some suggest that all women of childbearing age should know their CMV serostatus. [21][22][23][24] But on the other hand, American College of Obstetricians and Gynecologists [25] and Society for Maternal-Fetal Medicine, [26] recommend against routine serologic screening for CMV since there is no vaccine is available to prevent infection in seronegative women and in seropositive pregnant women, it is difficult to distinguish between primary infection, reinfection or reactivation and it is also diffucult to determine the time of the infection.…”
Section: Discussionsupporting
confidence: 44%
“…When we look at the studies conducted in Turkey, it is seen that this rate varies between 18.8% and 68.9% and is lower in the west and north of the country. [11] In the study conducted by Sirin et al between 2014 and 2016 in Izmir, it was stated that this rate was 32.2% and it was emphasized that Toxoplasma IgG positivity varied between 30.3% and 69.5% in studies conducted in Turkey. [10] Toxoplasma IgG positivity was reported as 22% in a study covering 2015-2017 in Bolu and 37.6% in a study covering the years 2012-2013 in Van.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations